Study on the cost allocation method to maximize the benefit of e‐commerce enterprises in the cloud computing environment. (5th June 2020) - Zhao, Jinfang
Summary: Cloud computing is a brand‐new IT service delivery model. It is a key strategic technology and means to lead the innovation of the information industry in the future. It can effectively solve the dynamic demand and final cost of e‐commerce enterprise resources, and it can reduce costs for e‐commerce enterprises to improve management, promote information development, and achieve resource integration. It is a key factor in shaping and enhancing the competitiveness of enterprises. Fuzzy paradigm should be understood and used at the level of world view and methodology, and should be recognized that it has different forms and properties in different disciplines. Based on the cloud computing environment, this article proposes a task allocation model, taking into account the utility functions of different users, and maximizing the overall terminal benefits by assigning computational tasks on a large number of terminals to virtual machine instances. The simulation results show that the overall benefit of the terminal under this allocation model is significantly higher than that of the overall terminal under the centralized task allocation model.